The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1111/j.1476-5381.1983.tb09362.x
|View full text |Cite
|
Sign up to set email alerts
|

Neostigmine augments responses of the rat anococcygeus muscle to field stimulation

Abstract: The effects of neostigmine on noradrenergic transmission have been studied in the field stimulated, isolated anococcygeus muscle of the rat. In those muscles where the excitatory response to field stimulation was not completely inhibited by guanethidine (5 × 10−6 to 10−5m) or phentolamine (10−6m), atropine (5 × 10−8m) gave no further inhibition of the response. The shape of the response to field stimulation was altered in a dose‐dependent manner by neostigmine (5 × 10−7 to 5 × 10−6m), such that a ‘shoulder’ ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Although histochemical techniques have failed to demonstrate butyryl or acetylcholinesterase in the rat anococcygeus (Gillespie, 1972;Bumstock et al, 1978), cholinesterase activity has been demonstrated colorimetrically (Gibson & Pollock, 1975;Smith & Spriggs, 1979) and the ability of neostigmine to potentiate responses to acetylcholine (but not to carbachol) confirmed (Gillespie & McGrath, 1974). The present study demonstrates that the potentiating effects of neostigmine were limited to the contractile responses to cholinomimetics and appeared to be correlated with a susceptibility to cholinesterase, i.e.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Although histochemical techniques have failed to demonstrate butyryl or acetylcholinesterase in the rat anococcygeus (Gillespie, 1972;Bumstock et al, 1978), cholinesterase activity has been demonstrated colorimetrically (Gibson & Pollock, 1975;Smith & Spriggs, 1979) and the ability of neostigmine to potentiate responses to acetylcholine (but not to carbachol) confirmed (Gillespie & McGrath, 1974). The present study demonstrates that the potentiating effects of neostigmine were limited to the contractile responses to cholinomimetics and appeared to be correlated with a susceptibility to cholinesterase, i.e.…”
Section: Discussionsupporting
confidence: 45%
“…Recently, the role of ganglia in the innervation of the rat anococcygeus has been reinvestigated (McKirdy & Muir, 1978) and a ganglionated nerve plexus, lying on the surface of the muscle and through which some cholinergic synaptic transmission occurs, described. Cholinesterase activity has also been detected in the tissue (Gibson & Pollock, 1975;Smith & Spriggs, 1979). However, although Gillespie's original paper (1972) demonstrated atropinesensitive, acetylcholine-induced contractions and a subsequent study (Gillespie & McGrath, 1974) illustrated the ability of neostigmine to potentiate responses to acetylcholine, no further detailed studies on the muscarinic antagonist/agonist interaction have been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The dis tribution of the reaction products which was observed when this incubation period was used seems not to result from any artifact but supports previous colorimetric data reported on the presence of AChE activity in the muscle [Gibson and Pollock, 1975;Smith and Spriggs, 1979], At the electron microscopic level, it may also be possible that an iso-OMPA-resistant cholinesterase exists in some axons of both adrenergic and non-adrenergic categories in the anococcy geus muscle. As far as they were examined by electron microscopy, however, no heavily stained axons were found in the muscle, though moderately stained ones of both adrenergic and non-adrenergic categories were occasionally found after a longer incu bation of 30-60 min at 0°C.…”
Section: Discussionsupporting
confidence: 73%
“…The pres ence of AChE activity in endings containing large granular vesicles has been reported in the mammalian atrium though they were not regarded as NANC axons [Graf, 1967;Hirano and Ogawa, 1969], Bell [1969], on the other hand, suggested that some of the lightly stained axons in the main uterine artery of the guinea pig may be NANC in nature. In the rat anococcygeus, although AChE activity has been demonstrated colorimetrically [Gibson and Pollock, 1975;Smith and Spriggs, 1979], histochemical techniques have failed to demonstrate the enzyme [Gillespie, 1972;Burnstock et al, 1978]. The purpose of the present study is to demonstrate the localization of AChE in the anococcygeus using the thiocholine method of Karnovsky and Roots [1964] at both light and electron microscopic levels.…”
Section: Introductionmentioning
confidence: 99%